Neuropharmacological effects of Gastrodia elata Blume and its active ingredients - Dong Wang; Dong Wang; Wei Liu; MeiJuan Lu; Qiang Xu (Frontiers in Neurology)
Gastrodia elata Blume (GE), a traditional Chinese medicine clinically employed to treat neurological disorders, demonstrates therapeutic efficacy supported by robust clinical evidence. Nowadays, conventional pharmacotherapies for neurological conditions—such as cholinesterase inhibitors for Alzheimer’s or Ldopa for Parkinson’s—often provide limited symptom relief, exhibit side effects, and fail to halt disease w, underscoring the need for alternative strategies. The primary bioactive compounds of Gastrodia elata Blume (GE) include gastrodin, p-hydroxybenzyl alcohol, Vanillyl alcohol, Polysaccharides, and β-sitosterol. Modern research has demonstrated that GE and its active components exhibit neuropharmacological effects, including neuron protection, reduction of neurotoxicity, and promotion of nerve regeneration and survival. For example, Gastrodin, exerts neuroprotection by scavenging reactive oxygen species, suppressing pro-inflammatory cytokines, and enhancing GABAergic transmission, thereby alleviating oxidative stress and neuronal apoptosis. Vanillin, potentiates GABA receptor activity, enhancing inhibitory neurotransmission and reducing seizure susceptibility.GE polysaccharides modulate the gut-brain axis and suppress microglial activation, mitigating neuroinflammation. Current studies primarily focus on GE and its active ingredients for the treatment of neurological diseases such as Parkinson’s disease, Alzheimer’s disease, epilepsy, convulsions, depression, schizophrenia, as well as enhancing learning and memory, and preventing or treating cerebral ischemic injury. This review explores the neuropharmacological effects of GE and its active compounds, elucidates the underlying mechanisms, and suggests potential preventive and therapeutic strategies for neurological diseases using herbal remedies.